Autochthonous Bacterial Isolates Successfully Stimulate In vitro Peripheral Blood Leukocytes of the European Sea Bass (Dicentrarchus labrax) - Mladineo, Ivona; Bušelić, Ivana; Hrabar, Jerko; Radonić, Ivana; Vrbatović, Anamarija; Jozić, Slaven; Trumbić, Željka (Frontiers in Microbiology, 2016)
Commercially available probiotics are routinely administered as feed supplements in aquaculture important species. Among them, the European sea bass (Dicentrarchus labrax) is the most widely reared fish in the Mediterranean, whose rearing systems are highly variable between countries, affecting at some level the sustainability of production. After random isolation of autochthonous gut bacteria of the sea bass, their identification and pathogenicity testing, we have selected three potentially probiotic isolates; Pseudoalteromonas sp., Alteromonas sp. and Enterovibrio coralii. Selected isolates were tested and their immunostimulative efficiency was compared with a commercially available Lactobacillus casei isolate, inferring inflammatory, apoptotic and anti-pathogen response of sea bass' peripheral blood leukocytes (PBL). Phagocytic activity, respiratory burst, and expression of lysozyme, Mx protein, caspase 3, TNF-α, IL-10 genes was measured 1, 3, 5 and 12 h post-stimulation by four bacterial isolates to evaluate early kinetics of the responses. Best immunostimulative properties were observed in Pseudoalteromonas-stimulated leukocytes, followed by Alteromonas sp. and L. casei, while Enterovibrio coralii failed to induce significant stimulation. Based on such in vitro assay intestinal autochthonous bacterial isolates showed to have better immunostimulative effect in sea bass compared to aquaculture-widely used L. casei, and further steps need to engage tank and field feeding trials to evaluate long-term prophylactic suitability of the chosen isolates. A panel of biomarkers that represent pro-/anti-inflammatory, pro-/anti-apoptotic and anti-bacteria/viral responses of the fish should be taken into consideration when evaluating the usefulness of the potential probiotic in aquaculture.